(untitled) (Journal of Medical Device Technology, 2024)
This review explores the current applications and future potential of 3D bioprinting in tissue engineering. Key bioprinting techniques including inkjet, extrusion, and laser-assisted methods are discussed, highlighting their advantages and limitations. The review examines various bioink materials, categorized into natural polymers, synthetic polymers, and decellularized extracellular matrix, evaluating their properties and suitability for different tissue types. Current applications in vascular, cartilage, and cancer tissue engineering are analyzed, showcasing the versatility of 3D bioprinting. Despite significant progress, challenges remain, including improving printing resolution, vascularization of larger constructs, and maintaining cell viability during the printing process. Future perspectives focus on enhancing the mechanical properties of bioprinted tissues, developing novel bioprinting methods, and incorporating vascularization-promoting factors. This review provides a comprehensive overview of the state-of-the-art in 3D bioprinting for tissue engineering, evolution to regenerative medicine and drug discovery.